2011
DOI: 10.1080/00918369.2011.540184
|View full text |Cite
|
Sign up to set email alerts
|

Using Hegemonic Masculinity to Explain Gay Male Attraction to Muscular and Athletic Men

Abstract: This article reviews relevant research on male homosexual attraction. Utilizing masculinity as its theoretical frame, the authors use childhood experiences with both fathers and peers, the gay community's inculcation of heteronormative ideologies, and the gay media's adherence to masculine prototypes, to provide causal explanations for the appeal of muscular, lean, and athletic physiques. While the authors acknowledge that not all individuals within the gay community look toward muscularity and athleticism as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 54 publications
1
47
0
Order By: Relevance
“…Adams, Braun and McCreanor (2014), for example, found that beauty, which included having a good body, was valued in relationships between gay men, and Lanzieri and Hildebrandt (2011) also discussed the appeal of muscularity for some gay men in terms of their sexual attraction to other similarly built men.…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…Adams, Braun and McCreanor (2014), for example, found that beauty, which included having a good body, was valued in relationships between gay men, and Lanzieri and Hildebrandt (2011) also discussed the appeal of muscularity for some gay men in terms of their sexual attraction to other similarly built men.…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…As Lanzieri & Hildebrandt (2011) have suggested, "men are consistently seeing more images of physically fit and toned males in different advertisement genres. Even today's action toys are depicted as more muscular than they were 25 years ago" (p. 285).…”
Section: Introductionmentioning
confidence: 92%
“…In body type, style, and dress, gay men counteract traits that would be considered feminine (Lanzieri & Hilderbrandt, 2011). Emphasis on increasing the size of the upper chest, and muscles reinforces this (Lanzieri & Hildebrandt, 2011). Male femininity is also symbolically constructed in the sense that being effeminate, a twink, or a bottom are seen as the embodiments of femininity (Schippers, 2007).…”
Section: Masculinity and Femininitymentioning
confidence: 99%
See 2 more Smart Citations